2005
DOI: 10.1007/bf02867412
|View full text |Cite
|
Sign up to set email alerts
|

Catalase: A repertoire of unusual features

Abstract: Catalases are antioxidant enzymes which catalyze the breakdown of hydrogen peroxide to water and oxygen, and are one of the oldest enzymes to be studied biochemically. The first crystal structure of a catalase appeared in the year 1980 and it revealed the tetrameric nature of the enzyme and presence of channels accessing the deeply buried active site heine. An interesting feature of the tetrameric structure is the characteristic interweaving or arm exchange of the subunits. The recent elucidation of the crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…3 B-D). A common property of catalases is that the N-and C-terminal ends of each monomeric subunit overlap, or ''interweave'' with other catalase monomers in the formation of a catalytically active tetramer (23,24). The N terminus affects tetramer formation; in Candida tropicans catalase (27) and E. coli catalase (28), small N terminus deletions (4-and 18-aa, respectively) reduce tetrameric accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 B-D). A common property of catalases is that the N-and C-terminal ends of each monomeric subunit overlap, or ''interweave'' with other catalase monomers in the formation of a catalytically active tetramer (23,24). The N terminus affects tetramer formation; in Candida tropicans catalase (27) and E. coli catalase (28), small N terminus deletions (4-and 18-aa, respectively) reduce tetrameric accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The N terminus of catalases is regarded as important in the formation of catalase tetramers (23,24). A silver-stained native gel showed that the Ser allele consisted almost entirely of the tetrameric form, whereas the equilibrium for the subunit asso- ciation in the Trp allele was significantly shifted to a smaller form (Fig.…”
Section: The Ser Catalase Allele Is More Active and Stable Than The Tmentioning
confidence: 99%
“…1b-d, respectively) which would imply that BA retention in the gingival tissue induces oxidative stress in the blood cytosol and is correlated to heme accumulation. Heme is a biomolecule that interacts with various apo-proteins giving rise to functional heme-proteins which include antioxidant (Chelikani et al 2005) and pro-oxidant (Espinosa et al 2009) enzymes. Build-up in cytosolic reactive oxygen species (ROS), like H 2 O 2 , triggers mitochondrial oxidative stress (Doughan et al 2008), whereas elevated mitochondrial ROS activates NADPH oxidase (Wosniak et al 2009).…”
Section: Ba Retention In the Gingival Tissue Induces Jugular Blood Cymentioning
confidence: 99%
“…The ROS are formed due to incomplete reduction of oxygen [254]. One type of ROS produced due to aerobic respiratory processes is hydrogen peroxide (H 2 O 2 ) [46]. Such oxidants can cause damage to lipids, proteins, and nucleic acids.…”
Section: Catalasementioning
confidence: 99%